Charge equalization controller algorithm for series-connected lithium-ion battery storage systems: Modeling and applications - Hannan M.A.; Hoque M.M.; Ker P.J.; Begum R.A.; Mohamed A. (MDPI AG, 2023)
Algorithms; Charging (batteries); Controllers; DC-DC converters; Efficiency; Electric inverters; Electric machine control; Equalizers; Ions; Lithium-ion batteries; Models; Pulse width modulation; Voltage control; Accurate modeling; Charge equalization; Controller algorithm; Existing controllers; Individual models; Renewable sources; State of charge; Sustainable energy; Battery management systems